93.3k views
3 votes
-2x + 4(4 + x) = 2x - 4(6 - 3x)

2 Answers

3 votes

1. -2x+4(4+x)

Like Terms : (-2x+x)(4+4)

-(1)x+8


2. 2x - 4(6-3x)

Like terms: (2x-3x)(6-4)

-(1)x+2


The answer shows that the problems are not equal to each other.


User Alexey Noskov
by
5.4k points
0 votes

Expand both sides to get



-2x + 16 + 4x = 2x - 24 + 18x


Bring all terms involving the unkown on the left and all constant terms on the right:



-2x + 4x -2x - 18x= - 24 -16


Simplify both sides summing like terms:



- 18x= -40


Divide both sides by -18 to get




x= (-40)/(-18) = (20)/(9)

User RichardAtHome
by
5.1k points